Do the Organizational Learning and Innovation Increase Organizational Performance on SMES? - Muhammad Sirojuddin Amin; Sudarmiatin Sudarmiatin; Agus Hermawan (Journal of Business and Management Review, 2023)
The post-pandemic economic situation forces companies to have breakthroughs to compete with competitors. This is a big enough problem for most MSMEs in Indonesia, including UD Sumber Dwi Jaya Food, which is engaged in the snack food sector in Lampung. Weak market conditions coupled with high raw material prices have forced UD Sumber Dwi Jaya Food to learn and innovate regarding its products. This will boost organizational performance so MSMEs can compete and increase their profits. This study aims to analyze the effect of organizational learning on organizational performance through organizational innovation. The population in this study were 38 employees of UD Sumber Dwi Jaya Food, all of whom were used as research samples. The method used in this research is using PLS-SEM analysis. Organizational learning can drive organizational performance because the organization can become a medium for employee learning and development. On the other hand, organizational innovation cannot encourage organizational performance or strengthen the relationship between organizational learning and organizational performance. The culture of innovation in SMEs is not going well, because low results for the innovation culture indicator. Not many innovations occur in SMEs, so this affects employee perceptions at work. This is interesting, considering that, in theory, organizational Innovation can improve organizational performance.